Capping of Silver Nanoparticles by Anti-Inflammatory Ligands: Antibacterial Activity and Superoxide Anion Generation - Paez-Collio, M; Paez-Collio, M; Castillo-Nara, A; Azocar-Guzman, M; Azocar-Guzman, M; Walter, M; Walter, M (Elsevier B.V., 2019)
Silver nanoparticles (AgNPs) have been widely recognized as antibacterial agents. However, its stability and activity over time have been poorly studied. In this work, the properties and characteristics of differently stabilized AgNPs were evaluated during a span of time. The surface capping agents were diclofenac (d), and ketorolac (k), which currently are used as anti-inflammatory in human medicine. On evaluating the size variation over time, it was observed that the AgNPs-k are the most stable, unlike the non-capped nanoparticles agglomerate and precipitate. UV–Vis spectroscopy analysis showed that the absorbance during time decreases for the three types of nanoparticles, but the decrease is less marked for the two types of anti-inflammatory-capped AgNPs. The rapid loss of the optical prop- erties of bare AgNPs, is mainly due to oxidation, agglomeration, and precipitation of this nanoparticles. The potential cytotoxicity of the AgNPs, evaluated through the formation of the superoxide anion using XXT, showed that both, AgNPs-k and AgNPs-d, generate the radical anion when the samples are irradiated with UV light at 365 nm. This effect appears associated with the capping agents, since the bare nanoparticles did not promote the formation of the superoxide anion. The antibacterial activity of the AgNPs throughout time, against two microorganisms (Escherichia coli and Staphylococcus aureus), was also evaluated. The results showed that capping agents played a decisive role in the antibacterial ability of AgNPs and also in enhancing the antibacterial activity over time. © 2019 Elsevier B.V.